Water-sensitive carbon dot as well as preparation method and application thereof

The water-sensitive carbon dots prepared by hydrothermal method are used as fluorescent probes to solve the problems of low sensitivity and high cost in water content detection in ethylene glycol, and achieve high sensitivity and low cost detection effects. They are suitable for coal-based ethylene glycol Detection of medium water content.

CN119307256AActive Publication Date: 2025-01-14BEIBU GULF UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411370894.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing water content detection methods in ethylene glycol have problems such as limited detection range, low sensitivity and high cost, especially in coal-based ethylene glycol, it is difficult to effectively detect the influence of water as an impurity.

Method used

Water-sensitive carbon dots were prepared by hydrothermal method, and citric acid and 1,1'-binaphthalene-2,2'-diamine were used as starting materials to synthesize fluorescent probes with high sensitivity for detection of ethylene glycol. Water content.

Benefits of technology

It realizes high sensitivity and low cost water content detection in ethylene glycol, has good linear relationships and high signal-to-noise ratio, and is suitable for quantitative analysis of polyester grade ethylene glycol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307256A_ABST
    Figure CN119307256A_ABST
Patent Text Reader

Abstract

The invention relates to a water-sensitive carbon dot and a preparation method thereof, and relates to the technical field of carbon nanotechnology. The preparation method comprises the following steps: adding a carbon source A and a carbon source B into a solvent to obtain a mixed solution, carrying out a hydrothermal reaction on the mixed solution, taking out the reacted mixed solution after the reaction is completed, centrifuging the reacted mixed solution to obtain a supernatant, mixing the supernatant with water, centrifuging, and removing filtrate to obtain the water-sensitive carbon dots. The invention provides a water-sensitive carbon dot as well as a preparation method and application thereof. The water-sensitive carbon dots are prepared through a hydrothermal method, the preparation method is simple, the cost is low, and the water-sensitive carbon dots can be well dispersed in ethylene glycol, are applied to detection of the content of water in ethylene glycol and have high actual value and good economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon nanotechnology, and in particular to a water-sensitive carbon dot and a preparation method and application thereof. Background Art

[0002] Ethylene glycol (EG) is an important organic chemical raw material, mainly used in the production of polyester, antifreeze and fine chemicals. The traditional process of ethylene glycol is produced by the ethylene method, and its price is greatly affected by the fluctuation of oil prices. With the development of the polyester industry, the demand for ethylene glycol has increased significantly. At present, coal-based ethylene glycol technology has occupied a certain share in the domestic and foreign markets, and has gradually expanded with the development of the coal chemical industry. Coal-to-ethylene glycol technology mainly produces ethylene glycol by oxalate hydrogenation. The reaction route is different from the traditional ethylene method, and new impurities are produced by side reactions. The emergence of new impurities has a certain impact on product purity, UV value and even the downstream polyester industry, and has attracted widespread attention in the industry. Therefore, it is of great significance and practical value to develop a highly sensitive method for detecting impurities in ethylene glycol.

[0003] However, in terms of the detection of ethylene glycol purity and impurities, the existing standards only provide analytical methods for alcohols in ethylene glycol, such as diethylene glycol, triethylene glycol and tetraethylene glycol. Detection methods for impurities such as 1,2-butanediol, 1,4-butanediol, 1,2-hexanediol and ethylene carbonate can also be established by chromatography. These methods face the problem of few detectable impurities, high detection limits and expensive precision instruments, which can no longer meet the analytical needs of the polyester industry for ethylene glycol. Water has been confirmed to be one of the impurities that affect the UV value of coal-based ethylene glycol, but there is a lack of simple, fast and efficient methods for detecting the water content in ethylene glycol. Fluorescence detection methods based on specific fluorescent materials are widely used in environmental monitoring and sensing fields due to their fast response speed, high signal-to-noise ratio and good sensitivity. A variety of methods for detecting water content in organic solvents based on fluorescent materials have been developed, but there is a lack of high-performance fluorescent materials suitable for detecting water content in ethylene glycol.

[0004] Carbon dots (CDs) have attracted a lot of attention in the fields of environmental monitoring, sensing and cell imaging due to their unique physicochemical properties, such as rich energy levels, tunable emission, good biocompatibility and diversified luminescence modes (DOI: 10.1016 / j.cej.2021.128999). Through heteroatom doping and surface functional group adjustment, CDs exhibit diversified luminescence, such as excitation-dependent luminescence, excitation-independent luminescence, aggregation-induced luminescence, etc. Among them, aggregation-induced luminescence CDs can overcome the aggregation luminescence quenching effect of CDs and are widely used in solid-state luminescence. Therefore, the luminescence performance of CDs can be regulated by adjusting the aggregation and dispersion state of CDs (DOI: 10.1021 / acssuschemeng.0c08652). By changing the aggregation and dispersion state of CDs by impurity solvents to turn on / quench the fluorescence of CDs, it is expected to achieve efficient quantitative analysis of impurity solvents. However, the luminescence of existing carbon dots is not easily adjusted due to the high viscosity of EG and the polyhydroxyl environment, which makes the development and design of carbon dots suitable for water content detection in EG still a challenge. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a water-sensitive carbon dot and its preparation method and application. The present invention prepares the water-sensitive carbon dot by hydrothermal method, the preparation method is simple, the cost is low, it can be well dispersed in ethylene glycol, and it can be used to detect the water content in ethylene glycol, which has high practical value and good economic benefits.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] The first object of the present invention is to provide a method for preparing water-sensitive carbon dots, comprising the following steps: adding carbon source A and carbon source B to a solvent to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction, taking out the mixed solution after the reaction is completed, centrifuging the mixed solution after the reaction to obtain a supernatant, mixing the supernatant with water and then centrifuging, removing the filtrate, and obtaining water-sensitive carbon dots.

[0008] The beneficial effects of the present invention are as follows: the present invention prepares water-sensitive carbon dots by a hydrothermal method, the preparation method is simple, the cost is low, the size distribution of the prepared carbon dots is uniform, and the preparation process is simple and easy to operate, which is conducive to large-scale production. The water content in polyester-grade ethylene glycol can be detected, and the water-sensitive carbon dots have high practical value and good economic benefits.

[0009] Furthermore, the usage ratio of the carbon source A, the carbon source B, and the solvent is (0.1-0.3) mol: (0.1-0.3) mol: 50 mL.

[0010] Furthermore, the carbon source A includes at least one of citric acid and sodium citrate; and the carbon source B is 1,1'-binaphthyl-2,2'-diamine.

[0011] Preferably, the carbon source A is citric acid, and the carbon source B is 1,1'-binaphthyl-2,2'-diamine.

[0012] Further, the solvent is glacial acetic acid.

[0013] The beneficial effect of adopting the above further scheme is: the present invention uses citric acid and 1,1'-binaphthyl-2,2'-diamine as starting materials, adopts a hydrothermal method to synthesize water-sensitive luminescent carbon dots, and uses them as fluorescent probes for detecting water content in ethylene glycol.

[0014] Furthermore, the centrifugal speed is 8000-10000 r / min, and the centrifugal time is 5-15 min.

[0015] Furthermore, the volume ratio of the supernatant to water is 1:(2-4).

[0016] The second object of the present invention is to provide a water-sensitive carbon dot.

[0017] Furthermore, the average particle size of the water-sensitive carbon dots is 2-4 nm.

[0018] The beneficial effect of adopting the above further scheme is that the carbon dots synthesized by the present invention have uniform size distribution, and the preparation process is simple and easy to operate, which is conducive to large-scale production.

[0019] The third object of the present invention is to provide an application of water-sensitive carbon dots, wherein the water-sensitive carbon dots are used as fluorescent probes for detecting the water content in ethylene glycol.

[0020] The beneficial effects of the present invention are as follows: the carbon dots of the present invention can be well dispersed in ethylene glycol, the fluorescence of the carbon dots in ethylene glycol is weak, and its intensity increases with the increase of the water content in the ethylene glycol solution, and has a good linear relationship in the range of 0 to 0.284% of water content, and has high detection sensitivity. Compared with other fluorescence detection methods, the present invention has a higher signal-to-noise ratio and higher detection sensitivity, and can be applied to the detection of water content in polyester-grade ethylene glycol, and has high practical value and good economic benefits.

[0021] Furthermore, the detection of the water content in the ethylene glycol is a quantitative detection, and the volume fraction of water in the ethylene glycol is in the range of 0 to 0.284%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The fluorescence excitation and emission spectra of the water-sensitive carbon dots in Example 1;

[0023] Figure 2is the UV-visible absorption spectrum of the carbon dots of Example 1;

[0024] Figure 3 is a transmission electron microscopy image of the carbon dots of Example 3;

[0025] Figure 4 is a particle size distribution diagram of the carbon dots of Example 3;

[0026] Figure 5 This is a high-resolution transmission electron microscopy image of the carbon dots of Example 3;

[0027] Figure 6 The full X-ray photoelectron spectrum and high-resolution C1s, N1s, and O1s images of the carbon dots of Example 3;

[0028] Figure 7 is a graph showing changes in the fluorescence intensity of the carbon dots in Example 3;

[0029] Figure 8 This is a linear fitting relationship diagram of the carbon dots in Example 3. DETAILED DESCRIPTION

[0030] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0031] Example 1: Preparation of water-sensitive carbon dots

[0032] (1) Add 50 mL of glacial acetic acid to a 100 mL beaker, then add 0.1 mol of citric acid and 0.1 mol of 1,1'-binaphthyl-2,2'-diamine, respectively, and stir magnetically for 5 min to obtain a colorless and clear mixed solution;

[0033] (2) The mixed solution was placed in a polytetrafluoroethylene-lined autoclave, reacted at 180° C. for 10 h, and after the reaction was completed, centrifuged at 10,000 r / min, and the supernatant was collected for later use;

[0034] (3) The supernatant and deionized water were mixed in a volume ratio of 1:3, and the precipitate was collected by centrifugation. The precipitate was vacuum freeze-dried to obtain a brown solid carbon dot powder.

[0035] The carbon dot powder prepared in Example 1 was dissolved in glacial acetic acid to obtain a colorless solution with a concentration of 8 mg / mL, which was used as a mother solution for standby use. The obtained mother solution was tested for fluorescence performance using a steady-state transient fluorescence spectrometer (FS5, Edinburgh, UK), and for UV-visible absorption spectrum using a UV-visible spectrophotometer (UV2600; Shimadzu). The results are as follows: Figure 1 , Figure 2 As shown:

[0036] Figure 1 The fluorescence excitation and emission spectra of the water-sensitive carbon dots prepared in Example 1 show that the water-sensitive carbon dots have weak fluorescence, with a maximum excitation wavelength of 340 nm and a maximum emission wavelength of 392 nm.

[0037] Figure 2 This is the UV-visible absorption spectrum of the water-sensitive carbon dots prepared in Example 1. The UV-visible absorption spectrum of the carbon dot solution has obvious absorption at around 240nm and 350nm.

[0038] Example 2: Preparation of water-sensitive carbon dots

[0039] (1) Add 40 mL of glacial acetic acid to a 100 mL beaker, then add 0.1 mol of citric acid and 0.1 mol of 1,1'-binaphthyl-2,2'-diamine, respectively, and stir magnetically for 5 min to obtain a colorless and clear mixed solution;

[0040] (2) The mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 180° C. for 10 h. After the reaction was completed, the mixture was centrifuged at 6000 r / min and the supernatant was collected for later use.

[0041] (3) The supernatant and deionized water were mixed in a volume ratio of 1:3, and the precipitate was collected by centrifugation. The precipitate was vacuum freeze-dried to obtain brown carbon dot powder.

[0042] Example 3: Preparation of water-sensitive carbon dots

[0043] (1) 0.1 mol of citric acid, 0.1 mol of 1,1'-binaphthyl-2,2'-diamine and 50 mL of glacial acetic acid were added to a 100 mL beaker and stirred magnetically for 5 min to obtain a colorless and clear mixed solution;

[0044] (2) The mixed solution was placed in a polytetrafluoroethylene-lined autoclave, reacted at 180° C. for 10 h, and after the reaction was completed, centrifuged at 8000 r / min, and the supernatant was collected for later use;

[0045] (3) The supernatant and deionized water were mixed in a volume ratio of 1:3, and the precipitate was collected by centrifugation. The precipitate was vacuum freeze-dried to obtain brown carbon dot powder.

[0046] The supernatant prepared in step (2) of Example 3 was subjected to high-resolution transmission electron microscopy testing. The results are as follows: Figure 3-5 As shown; the carbon dot powder obtained in step (3) of Example 3 was then tested by using an X-ray photoelectron spectrometer (Kratos AXISUltraDLD, Kratos Analytical Ltd). The results are as follows Figure 6 As shown; the carbon dot powder prepared in Example 3 was dissolved in glacial acetic acid to obtain a colorless solution, which was used as a mother solution (concentration of 8 mg / mL) for standby use, 200 μL of the mother solution was added to 2.8 mL of polyester-grade ethylene glycol to obtain a colorless and transparent carbon dot ethylene glycol solution, and its fluorescence intensity was detected; 0-0.284% deionized water was then added respectively, and the fluorescence performance was tested using a steady-state transient fluorescence spectrometer (FS5, Edinburgh, UK). The results are shown in Figure 7-8 shown.

[0047] Depend on Figure 3-8 We can get:

[0048] (1) Figure 3-5 As shown, the carbon dots obtained in Example 3 have a nearly spherical appearance (such as Figure 3 ), with an average particle size of about 2.75 nm (e.g. Figure 4 ), the interplanar spacing of carbon dots is 0.21nm (such as Figure 5 ), which belong to the 100 crystal planes of graphitized carbon, respectively, proving that the prepared material is carbon dots.

[0049] (2) Figure 6 As shown, the XPS spectrum of the carbon dot powder prepared in Example 3 shows that the carbon dots contain C (83.64%), N (8.96%), and O (7.41%) elements, and the high-resolution C1s, N1s, and O1s prove that the carbon dots contain a large number of hydroxyl, amino, and carbonyl functional groups.

[0050] (3) Figure 7-8 As shown in Figure 2, the maximum excitation wavelength is 340 nm, and the maximum emission wavelength is 392 nm. The fluorescence intensity of the carbon dot ethylene glycol solution increases significantly with the increase of water content. The optimal excitation wavelength is at 340 nm, and the optimal emission wavelength is at 392 nm (as shown in Figure 2). Figure 7 ). After adding 0-0.284% deionized water, the fluorescence intensity of the carbon dot ethylene glycol solution at the emission wavelength of 392nm has a good linear relationship with different contents of deionized water. The fitting equation is y=0.513+1.726C(Water%), and the correlation coefficient R 2 =0.998 (e.g. Figure 8 ).

[0051] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing water-sensitive carbon dots, characterized in that: The preparation method comprises the following steps: adding carbon source A and carbon source B into a solvent to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction, taking out the mixed solution after the reaction is completed, centrifuging the mixed solution to obtain a supernatant, mixing the supernatant with water and centrifuging, removing the filtrate, and obtaining water-sensitive carbon dots.

2. The method for preparing water-sensitive carbon dots according to claim 1, characterized in that: The usage ratio of the carbon source A, the carbon source B, and the solvent is (0.1-0.3) mol: (0.1-0.3) mol: 50 mL.

3. The method for preparing water-sensitive carbon dots according to claim 2, characterized in that: The carbon source A is at least one of citric acid and sodium citrate; and the carbon source B is 1,1'-binaphthyl-2,2'-diamine.

4. The method for preparing water-sensitive carbon dots according to claim 2, characterized in that: The solvent is glacial acetic acid.

5. The method for preparing water-sensitive carbon dots according to claim 1, characterized in that: The centrifugal speed is 8000-10000 r / min, and the centrifugal time is 5-15 min.

6. The method for preparing water-sensitive carbon dots according to claim 1, characterized in that: The volume ratio of the supernatant to water is 1:(2-4).

7. A water-sensitive carbon dot, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. The water-sensitive carbon dots according to claim 7, characterized in that: The average particle size of the water-sensitive carbon dots is 2-4 nm.

9. An application of water-sensitive carbon dots, characterized in that: The water-sensitive carbon dots described in claim 7 or 8 are used as fluorescent probes to detect the water content in ethylene glycol.

10. The use of water-sensitive carbon dots according to claim 9, characterized in that: The detection of the water content in the ethylene glycol is a quantitative detection, and the volume fraction of water in the ethylene glycol is in the range of 0 to 0.284%.

Citation Information

Patent Citations

  • Preparation method of carbon dot having high fluorescent quantum yield

    CN103045242A

  • Preparation method and product of full-color carbon dots for multi-color fluorescent printing

    CN108587615A

  • Peroxide fluorescence colorimetric dual-mode detection method based on carbon dot fluorescence inner filter effect

    CN112964686A

  • Nitrogen-sulfur-doped efficient red light emission carbon dot, preparation method and application thereof

    CN112980437A

  • Ethylenediamine-doped fluorescent carbon dots, preparation method thereof and application of ethylenediamine-doped fluorescent carbon dots in detection of copper ions in water body

    CN116606648A